Spontaneous vaginal delivery after a pregnancy complicated with Guillain-Barré syndrome - Başer Açıkgöz, Rabia (Journal of Surgery and Medicine, 2018)
Guillain-Barré syndrome (GBS) is a rarely encountered, acute autoimmune polyradiculoneuropathy which is usually severe and fulminant. Although it is considered not to have an impact on the prognosis of pregnancy, there is no consensus on its management particularly in pregnant women with advanced motor dysfunctions. Different obstetrical approaches have been suggested. Herein, we discussed a case, which has been diagnosed with GBS in the 3rd trimester in our clinic and gave birth to a healthy infant via spontaneous vaginal delivery without any intrapartum or postpartum maternal complication. Patient presentation, diagnosis, treatment and outcome as well of review of the literature will be discussed.